2021
DOI: 10.3390/f12081106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis and Potential Distribution Prediction of Sophora moorcroftiana Endemic to Qinghai–Tibet Plateau, China

Abstract: Sophora moorcroftiana (Benth.) Baker is an endemic woody species distributed in the Qinghai–Tibet Plateau (QTP), a part of the world characterized by high altitude and cold weather. In this study, the genetic diversity of S. moorcroftiana was evaluated based on 300 representative samples of 15 populations using 20 polymorphic SSR markers, and its potential distribution was predicted according to 19 bioclimatic factors using MaxEnt modeling. Results showed the population genetic diversity of S. moorcroftiana wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Studies about trees in the QTP region showed that altitude, rather than other environmental factors, was the key factor affecting genetic diversity (e.g. [53,54]), but it is not the scenario we observe in the three herbaceous gentians, although a limited number of populations were tested in this study. Finally, since our analysis did not include other environmental variables, such as soil characteristics, composition and structure, we cannot rule out that habitat adaptation to these environmental variables played a significant role in promoting genetic divergence in the three gentians, as was probably the case in European gentians [25].…”
Section: Did Climatic Preferences Contribute To Divergence?mentioning
confidence: 58%
“…Studies about trees in the QTP region showed that altitude, rather than other environmental factors, was the key factor affecting genetic diversity (e.g. [53,54]), but it is not the scenario we observe in the three herbaceous gentians, although a limited number of populations were tested in this study. Finally, since our analysis did not include other environmental variables, such as soil characteristics, composition and structure, we cannot rule out that habitat adaptation to these environmental variables played a significant role in promoting genetic divergence in the three gentians, as was probably the case in European gentians [25].…”
Section: Did Climatic Preferences Contribute To Divergence?mentioning
confidence: 58%
“…Previous studies on S. moorcroftiana have mainly focused on its population distribution ( Liu et al., 2020 ; Xin et al., 2021 ; Yang et al., 2021 ), soil seed banks ( Zhao et al., 2007 ), medicinal functions ( Wang et al., 2014 ; Luo et al., 2018 ), analysis of transcriptome ( Li et al., 2015 ) and verification of gene functions ( Li et al., 2017 ). In this study, we report, for the first time, the phenotypic and genotypic variations in nine seed traits and the mean repeatability of 15 accessions of S. moorcroftiana .…”
Section: Discussionmentioning
confidence: 99%
“…Because smaller seeds are usually dispersed further by abiotic factors such as water and wind. This is closely related to the external environment such as the altitude, slope, temperature and rainfall of the population ( Liao et al., 2020 ; Yang et al., 2021 ). This was also supported by the correlations between seed traits and altitude and temperature in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the value, the higher the reliability of the distinction between suitable and unsuitable habitats. AUC = 0.5 indicated that the model fails to judge completely, less than 0.8 indicated a low reliability and 0.9~1.0 indicated a high credibility [49]. The evaluation criteria for Kappa value and TSS were excellent, 1.0-0.85; very good, 0.7-0.85; good, 0.55-0.7; fair, 0.4-0.55; fail, <0.4 [50][51][52].…”
Section: Model Building Optimization and Evaluationmentioning
confidence: 99%
“…Due to gymnosperms low migration rate, serious fragmentation of suitable habitats and frequent human activities, it may not be able to quickly adapt to suitable range changes. Therefore, G. pensilis within and outside nature reserves must be managed through in situ and ex situ conservation, habitat wetland conservation, assisted migration and sapling conservation to avoid extinction [29,42,49,91].…”
Section: Conservation Managementmentioning
confidence: 99%